Learning Experience of Pre-Service Physics Teachers in Developing Simple Project Loaded by Life Skills - Susilawati, S.; Khoiri, N.; Wijayanto, W.; Masturi, M.; Xaphakdy, S. (Jurnal Pendidikan IPA Indonesia, 2018)
This research aims to reveal the experience profile of future Physics teachers in developing simple multi-loaded life skill project. The research method used was a descriptive method with 62 future Physics teachers as the research subject. Based on observations, interviews, and questionnaires, it was drawn descriptions of the future teachers’ experiences in developing a simple project. The future teachers were assessed based on some Physics indicators such as project design, project creation, data collection, data analysis, and creativity. The results of the project preparation descriptions obtained by the experience data of future Physics teachers indicate the highest score of 4.8 (96%) on the indicator of schedule making, while the lowest score was 2.9 (58%) on the indicators of formulating the product benefits, preparing the feasibility analysis and analyzing the environmental impact. The results show that future Physics teachers got the highest score of 4.6 (93%) on data adjustment for experimental purposes indicator, and the lowest score of 2.8 (55%) on designing tools and materials indicator. Based on the Physics props trial, it was obtained the highest score of 4.5 (89%) on the indicator of analyzing the baseline data, while the lowest score of 2.9 (58%) was on the variation test variables. Positive feedback about time-management in completing the project, the ability to identify the topic of the project, the ability to find ideas to support the completion of the project, the ability to test the tools, and the ability to make progress reports on project completion were derived from the interviews. The highest score of students’ responses to project completion was 4.8 (95%) on the second data collection indicator and the lowest was 3.2 (64%) on the instrument material design indicator.